Analysis of the Simultaneous Problems of Poverty and Gross Domestic Product (GDP) as Macroeconomic Factors in a Developing Country - Masyhuri, Muhammad (PT. Riset Press International, 2023)
When analysing macroeconomic factors using an econometric approach that attempts to determine the successful economic development of countries, such as in the analysis of poverty and gross domestic product (GDP), problems have been repeatedly encountered in considering the variables involved simultaneously. To overcome this problem, it is necessary to use the two-stage least squares (2SLS) method as the best estimator by applying the simultaneous equation model. The objective of this study is to analyse the simultaneous equation model between poverty and GDP in a developing country such as Indonesia. The macroeconomic data sources used for this study are secondary time series data from 1990 to 2017 obtained from Indonesia Statistics Agency, IMF, UNDP and World Bank. The result shows that there is strong evidence that poverty and GDP act simultaneously or endogenously in the model. From the results, it is recommended that in order to achieve higher GDP in the future, the Indonesian government should pay more attention to alleviating poverty rates, reducing unemployment rates, lowering merchandise imports, and improving economic growth in addressing macroeconomic problems in the country.